Ecology and Neurophysiology of Sleep in Two Wild Sloth Species - Voirin, Bryson (Associated Professional Sleep Societies, LLC, 2014)
STUDY OBJECTIVES: Interspecific variation in sleep measured in captivity correlates with various physiological and environmental factors, including estimates of predation risk in the wild. However, it remains unclear whether prior comparative studies have been confounded by the captive recording environment. Herein we examine the effect of predation pressure on sleep in sloths living in the wild. DESIGN: Comparison of two closely related sloth species, one exposed to predation and one free from predation. SETTING: Panamanian mainland rainforest (predators present) and island mangrove (predators absent). PARTICIPANTS: Mainland (Bradypus variegatus, five males and four females) and island (Bradypus pygmaeus, six males) sloths. INTERVENTIONS: None. MEASUREMENTS AND RESULTS: Electroencephalographic (EEG) and electromyographic (EMG) activity was recorded using a miniature data logger. Although both species spent between 9 and 10 h per day sleeping, the mainland sloths showed a preference for sleeping at night, whereas island sloths showed no preference for sleeping during the day or night. Standardized EEG activity during nonrapid eye movement (NREM) sleep showed lower low-frequency power, and increased spindle and higher frequency power in island sloths when compared to mainland sloths. CONCLUSIONS: In sloths sleeping in the wild, predation pressure influenced the timing of sleep, but not the amount of time spent asleep. The preference for sleeping at night in mainland sloths may be a strategy to avoid detection by nocturnal cats. The pronounced differences in the NREM sleep EEG spectrum remain unexplained, but might be related to genetic or environmental factors. CITATION: Voirin B; Scriba MF; Martinez-Gonzalez D; Vyssotski AL; Wikelski M; Rattenborg NC. Ecology and neurophysiology of sleep in two wild sloth species. SLEEP 2014;37(4):753-761.